One Kid, One Only Kid - Hana Wirth-Nesher (The Princeton University Library Chronicle, 2002)
Background Reduced bone mineral density and fractures are well-established complications in advanced CKD, but the role of mild to moderate CKD and albuminuria remain unclear. We assessed whether albuminuria modifies the association between CKD stage and bone mineral density and risk of major osteoporotic fractures. Methods Participants from the HUNT and Tromsø studies (n=31,341) provided data on CKD (classified by eGFR G1 (≥90), G2 (60-89), G3a (45-59), and G3b/G4 (<45 mL/min/1.73 m2)), albuminuria (defined by albumin-creatinine ratio: A1 (<30 mg/g) and A2/A3 (≥30 mg/g)) and fractures. We estimated mean bone mineral density differences and hazard ratios (HRs) using linear mixed models and Cox regression. Effect modification was assessed using an interaction term and Wald test. Linear combinations were used to estimate pairwise contrasts between CKD-albuminuria categories (reference: CKD G1 and albuminuria A1), and within CKD stages. Results Compared with G1, bone mineral density was modestly lower and fracture risk was highest in G3b/G4 (HR 1.40; 95% confidence interval [CI]: 1.12 to 1.74). Albuminuria (A2/A3) was associated with both lower bone mineral density and slightly higher fracture risk compared with A1, independent of eGFR. Patterns differed by albuminuria category: In A1, bone mineral density remained stable across CKD stages, whereas in A2/A3 it was progressively lower from G3a onward. Fracture risk increased with CKD severity in both albuminuria categories and was consistently higher in A2/A3 across advancing CKD stages. In G3b/G4, HRs were 1.27 (CI: 0.96 to 1.68) in A1 and 1.58 (CI: 1.07 to 2.36) in A2/A3. Conclusions Lower bone mineral density was observed in advanced CKD with albuminuria. Fracture risk increased from CKD stage G3a and tended to be higher in the presence of albuminuria, indicating an association between albuminuria and impaired bone health.